2021
DOI: 10.1111/jon.12861
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain network reorganization in HIV infection

Abstract: Background and Purpose To investigate the reorganization of the central nervous system provided by resting state‐functional MRI (rs‐fMRI), graph‐theoretical analysis, and a newly developed functional brain network disruption index in patients with human immunodeficiency virus (HIV) infection. Methods Forty HIV‐positive patients without neurological impairment and 20 age‐ and sex‐matched healthy controls underwent rs‐fMRI at 3T; blood sampling was obtained the same day to evaluate biochemical variables (absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(131 reference statements)
0
6
0
Order By: Relevance
“…These markers of AD currently include neurodegenerative metrics obtained from MRI (e.g., less GMV) and PET (e.g., abnormal amyloid and tau depositions; Jack et al, 2018 ). Potential future directions might be to combine the Frascati criteria with emerging neuroimaging markers of HAND, including GMV as demonstrated in the present study, as well as functional MRI ( Ances et al, 2009 , Nguchu et al, 2021 , Plessis et al, 2014 , Hall et al, 2021 , Minosse et al, 2021 ) and magnetoencephalography ( Spooner et al, 2020 , Lew et al, 2018 , Wiesman et al, 2018 , Wilson et al, 2017. , Becker et al, 2012a , Becker et al, 2012b ).…”
Section: Discussionmentioning
confidence: 91%
“…These markers of AD currently include neurodegenerative metrics obtained from MRI (e.g., less GMV) and PET (e.g., abnormal amyloid and tau depositions; Jack et al, 2018 ). Potential future directions might be to combine the Frascati criteria with emerging neuroimaging markers of HAND, including GMV as demonstrated in the present study, as well as functional MRI ( Ances et al, 2009 , Nguchu et al, 2021 , Plessis et al, 2014 , Hall et al, 2021 , Minosse et al, 2021 ) and magnetoencephalography ( Spooner et al, 2020 , Lew et al, 2018 , Wiesman et al, 2018 , Wilson et al, 2017. , Becker et al, 2012a , Becker et al, 2012b ).…”
Section: Discussionmentioning
confidence: 91%
“…This interpretation is further supported by our observation that HIV-associated RAI reductions were primarily driven by PLWH (vs. HIV− participants) presenting with higher SN-DMN synchrony. Prior work demonstrating altered network organization among PLWH ( Abidin et al, 2018 ; Hall et al, 2021 ; Minosse et al, 2021 ) has also often highlighted alterations involving the DMN ( Thomas et al, 2015 ; Zhuang et al, 2017 ). For example, one study found that treatment naïve PLWH displayed significantly reduced rsFC within the DMN when compared with controls ( Zhuang et al, 2017 ), while another study utilizing graph theoretic metrics found alterations in closeness centrality (a metric indicating connectiveness with the rest of the brain) within the DMN and frontoparietal network among PLWH ( Thomas et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…People living with HIV (PLWH) can also have neurological symptoms. The virus can cross the blood-brain barrier during the acute phase, with the migration of infected monocytes from the bloodstream into the CNS and infect neighbouring cells, such as microglia and astrocytes 34 . The antiviral cytokines present in the brain during infection control the viral replication in the CNS 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Neurons are not killed directly by a viral infection, but viral proteins induce the production of cytokines such as IFN-γ, TNF-α, and IL-1β which are neurotoxic. A study found that the JAK/STAT pathway, a key regulator of inflammatory and apoptotic signalling, is elevated in HIV-1-infected brains progressing to HAND 34 . This pathway can be inhibited by the epigallocatechin-3-gallate (EGCG) present in green tea, resulting in a decrease of inflammatory cytokines and the consequent mitigation of neuronal damage in the cortical regions of mouse brains, as compared to controls 45 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation